Biostratigraphy of the Early Cretaceous Mauddud Formation in Ratawi Oilfield, Basrah Governorate, Southern Iraq - Ezzulddin, Leqaa N.; Ibrahim, Yasamin K. (Iraqi Journal of Science, 2022)
The biostratigraphy of the Early Cretaceous Mauddud Formation was studied in the Ratawi Oilfield, Basra Governorate, southern Iraq, using integrated borehole data set (core and cutting samples and well logs) in two drilled wells to analyze the biostratigraphy of the formation. One hundred eighty-three slides for both selected wells were investigated. The formation is composed of light grey dolomitized limestone and pseudo-oolitic creamy limestone with green to bluish shale. Three biozones were discriminated, these are: Orbitolina qatarica range zone; Orbitolina sefini range zone and Orbitolina concava range zone. The age of these biozones extends to include the Late Albian (Orbitolina qatarica); Late Albian-Early Cenomanian (Orbitolina sefini) and Early Cenomanian for (Orbitolina concava) zone. The fossils occurred are Conicorbitolina conica, Coral, gastropoda, Miliolids, Nezzazata , Neoiraqia convexa, orbitolina discoidia, Orbitolina kurdica, Spiroluculina sp., trocholina sp .